Method to estimate cancer overdiagnosis with prostate screening - Hu, Jiarui (My University, 2018)
Aim: Several studies have tried to quantify overdiagnosis of prostate cancer with Prostate-specific antigen(PSA) screening, but estimates vary widely. This study aims to evaluate the degree of overdiagnosis of prostate cancer with 10 or 14 follow-up years after the stop of screening in Finland. Methods: We selected 80379 men aged 55-69 years who were randomized to a screening or a control arm, distinguishing four birth cohorts: 1941-44,1937-40, 1933-36 and 1929-32. The first PSA screening test occurred during1996-1999. Men without detected as prostate cancer in the previous screening would be invited to the next screening 4 years later. The estimate of overdiagnosis is the ratio of the cumulative excess incidence to the cumulative incidence of prostate cancer in the screened group after the year-specific incidence became stable. Results: The patterns of all incidences in these four cohorts have not become stable yet, and the difference of cumulative incidence in the current longest follow- up years is the best estimate of overdiagnosis so far. Conclusion: Overdiagnosis rates of prostate cancer in people who received screening in Finland was estimated as 2.27%,15.4%, 11.4%, and 10.2% for 1929-32, 1933-36,1937-40, and 1941-44 cohorts, respectively.
Keywords: cancer overdiagnosis; prostate cancer